14-weeks combined exercise epigenetically modulated 118 genes of menopausal women with prediabetes - Yumi Noronha, Natália; da Silva Rodrigues, Guilherme; Harumi Yonehara Noma, Isabella; Fernanda Cunha Brandao, Camila; Pereira Rodrigues, Karine; Colello Bruno, Alexandre; Sae-Lee, Chanachai; Moriguchi Watanabe, Lígia; Augusta de Souza Pinhel, Marcela; Mello Schineider, Isabelle; Luciano de Almeida, Mariana; Barbosa Júnior, Fernando; et al. (Frontiers in Endocrinology, 2022)
Background: Pre-diabetes condition precedes the Diabetes Mellitus (DM) disease and is a critical period for hyperglycemia treatment, especially for menopausal women, considering all metabolic alterations due to hormonal changes. Recently, the literature has demonstrated the role of physical exercise in epigenetic reprogramming to modulate the gene expression patterns of metabolic conditions, such as hyperglycemia, preventing DM development. In the present study, we hypothesized that physical exercise training could modify the epigenetic patterns of women with poor glycemic control. Methods: 48 post-menopause women aged 60.3±4.5 years were divided according to the fasting blood glucose levels into two groups: Prediabetes Group, PG (n=24) and Normal Glucose Group, NGG (n=24). All participants performed 14 weeks of physical exercise three times a week. The Infinium Methylation EPIC BeadChip measured the participants’ Different Methylated Regions (DMRs). Results: Before the intervention, the PG group had 12 DMRs compared to NGG. After the intervention, five DMRs remained different. Interestingly, when comparing the PG group before and after training, 118 DMRs were found. The enrichment analysis revealed that the genes were related to different biological functions such as energy metabolism, cell differentiation, and tumor suppression. Conclusion: Physical exercise is a relevant alternative in treating hyperglycemia and preventing DM in post-menopause women with poor glycemic control.